The classroom as a space for the construction of linguistic competence - Castellanos Sánchez, Leinny Yasmin; Padilla García, Dianna Paola (Rastros Rostros, 2023)
Working on competencies in the classroom is an exercise that requires a clear discipline, both from the teacher and the student, and an appropriation of the subject matter, in order to be able to address the different strategies that need to be implemented if the efficiency of those involved is to be achieved.
Keywords: linguistic competence; strategies